2010
DOI: 10.1016/j.vetimm.2009.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the cytokine and maturation responses of pure populations of porcine plasmacytoid dendritic cells to porcine viruses and toll-like receptor agonists

Abstract: Plausible representatives of plasmacytoid dendritic cells (pDCs) in pigs have been characterized as being CD4(hi)CD172(lo). Due to their paucity in blood, we utilized novel fluorescent-activated cell sorting procedures to isolate them from PBMC. The resultant subset was greater than 98% homogeneous in regards to the selected phenotype and contained the preponderance of individuals secreting IFN-alpha after exposure to a known stimulant, transmissible gastroenteritis virus (TGEV). In addition to being a potent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 69 publications
4
54
0
Order By: Relevance
“…Independent of this issue requiring further clarification, pDC are more likely to promote Th1 responses through secretion of type I IFNs, IL-12 and TNF-α [2]. We and others have also found this profile of cytokines for porcine pDC [1], [34].…”
Section: Discussionmentioning
confidence: 55%
“…Independent of this issue requiring further clarification, pDC are more likely to promote Th1 responses through secretion of type I IFNs, IL-12 and TNF-α [2]. We and others have also found this profile of cytokines for porcine pDC [1], [34].…”
Section: Discussionmentioning
confidence: 55%
“…TLR2), poly(I:C) (?TLR3) (Auray et al, 2010), lipopolysaccharide (LPS ? TLR4) Uddin et al, 2012), imiquimod (?TLR7/8) (Calzada-Nova et al, 2010), CpG ODN (?TLR9) (Auray et al, 2010;Calzada-Nova et al, 2010;Dar et al, 2010), and muramil dipeptide (MDP ? NOD) (Jozaki et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to humans, imiquimod could not only activate TLR7 but also TLR8 in the pig, showing altered receptor specificity across species (Zhu et al, 2008). Calzada-Nova et al found an enhanced production of various cytokines (IFN-a, IFN-c, IL-2, IL-6, IL-8, IL-12, and TNF-a) after plasmacytoid DCs (pDCs) were stimulated with both imiquimod and the TLR9 ligand CpG ODN (Calzada-Nova et al, 2010). CpG ODN additionally increased the expression of chemokine receptors on monocyte derived DCs (MoDCs) and blood DCs (bDCs) (Auray et al, 2010) as well as altering the general DC morphology of cultured sorted plasmacytoid (pDCs) compared to unstimulated cultures (Calzada-Nova et al, 2010).…”
Section: Toll-like Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since PRRSV can infect DCs (Loving et al, 2007), the response of DCs to PRRSV infection is of interest. The production of type I IFNs by pDCs is severely suppressed during PRRSV infection (Baumann et al, 2013;Calzada-Nova et al, 2010). Furthermore, the pDCs activation, which is featured by the increase of CD80/86 expression and cell-type development, is not seen by PRRSV (Calzada-Nova et al, 2011).…”
Section: Porcine DC Response To Prrsv Infectionmentioning
confidence: 98%